MUSIKALISASI MATERI SEL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS XI IPASMAN 1 UPAU TABALONG MELALUI MODEL PEMBELAJARAN KOOPERATIF - Puji Asrini, Dwi Nopyanti (Vidya Karya Jurnal Kependidikan, 2014)
Research on musical of cells material through cooperative learning model has been implemented with the purpose: (1) Increase motivation to learn (2) Improve student learning outcomes (3) Increase the management of learning (4) Increase the activity of the teacher (5) study the response of the students. The research design is class action research with two cycles. Research subject were students of class XI Science SMAN 1 Upau totaling 17 students. Data were collected from test instruments, questionnary and observation. The research showed: (1) Students learning motivation increase. It can be seen from the score of sudentsâ activitiy (4,51, very active) and the score of student motivation (4,53, very good;) (2) The improvement of students learning outcomes of cognitive aspect (classical mastery by 23,53% to 92,86%) and affective aspect. (3) Teacher learning management increased to excellent category (score 3,86). (4) Teacherâs activity increased to active (score 2,7%). (5) All students showed a positive response to the model.